The Influence Of School Leadership Style And Teacher Work On Teacher Performance Satisfaction - Yuniarti, Yuniarti; Ahmad, Syarwani; Fitriani, Yessi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to describe and analyze the effect of three variables which include the influence of the principal's leadership style and job satisfaction on teacher performance. This research is a type of quantitative research. The population in this study amounted to 90 people who came from a number of public elementary schools in the District of Sosoh Buay Rayap. The data collection techniques used were questionnaires, observation, interviews, and documentation. The data analysis technique used inferential statistics which included normality, homogeneity, linearity, simple linear correlation test, multiple correlation test, T test, and f test. The results of this study are (1) principal leadership style has a positive effect on teacher job satisfaction, (2) job satisfaction has a positive effect on teacher performance, and (3) principal leadership style and job satisfaction simultaneously have a positive effect on teacher performance.